Artificial Intelligence in Bid Rigging Case Settlement Process: Law and Ethic (Open Society Conference, 2025)
Bid rigging is one of the forms of unfair business competition. One of the indications of bid rigging is similar documents. Artificial Intelligence (AI) can be used in detecting indications of bid rigging make it a challenge as well as a potential renewal of detection tools in the bid rigging case settlement. This causes the need to regulate the concept of using Artificial Intelligence to ensure the settlement of bid rigging can run effectively. The process of bid rigging case settlement also needs to consider ethics. This study is a normative juridical research using statutory approach and conceptual approach. The data used is secondary data. The data was collected by literature study method, analyzed by qualitative normative method, and presented descriptively. This study aims to know that Artificial Intelligence can be applied as a tool to detect the similiarity of bidding documents so that the commitee can immidiately identify the potential of bid rigging including at the stage of: research or monitoring of business actors and preliminary examination. The use of Artificial Intelligence technology needs to pay attention to the ethics in the implementation of Artificial Intelligence technology including inclusiveness, humanity and security, transparency, credibility and accountability.